Studying a study and testing a test reading evidence-based health research - Riegelman, Richard K.; Nelson, Benjamin A.; Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer Health, 2020)
'Learning evidence-based medicine is a requirement in medicine, PA, NP, pharmacy, and most other health practitioner fields. For example, most PA programs have required coursework in evidence-based programs during the first (didactic) year; medical students have this content woven into their clinical medicine coursework'--
Electronic reproduction.
Keywords: Medical literature -- Evaluation; Medicine -- Research -- Evaluation; Evidence-based medicine; Biometry; Biometry; Evidence-Based Medicine -- methods; Epidemiologic Methods